Research of mechanical properties of the sintered samples from electro-erosion cobalt-chromium powder - V. Ageev, E; Yu. Altukhov, A; V. Pikalov, S; I. Serebrovskii, V; I. Safronov, R (International Journal of Engineering and Technology, 2018)
The main requirement for powders for additive 3d technologies is the spherical shape of the particles. Such particles are most compactly packed into a certain volume and ensure the "fluidity" of the powder composition in the supply systems of the material with minimal resistance. Proceeding from the peculiarities of the methods for the production of spherical powders with the aim of obtaining spherical granules of regulated granularity, the technology of electroerosive dispersion is proposed, which is characterized by relatively low energy costs and ecological purity of the process. Based on the results of the studies aimed at investigating the mechanical properties of sintered samples from cobalt-chrome powders obtained for additive technologies by electroerosive dispersion, it was established that the average Vickers hardness of sintered samples is 14,63 Gpa; the porosity of the sintered samples is 6,15%.